1279. In Vitro Activity of Nacubactam (OP0595) Alone and in Combination with β-Lactams against β-Lactamase-Producing Enterobacterales Isolated in Japan. (31st December 2020) - Nagira, Yu; Yamada, Keiko; Okade, Hayato; Senju, Nami; Tsutsumi, Yuko; Tabata, Yuji; Kato, Kazuhiko
Abstract: Background: Nacubactam (NAC) is a novel serine β-lactamase inhibitor in clinical development, and inhibits Ambler class A, class C, and some class D β-lactamases. In addition, it has penicillin-binding protein (PBP) 2-dependent antibacterial activity and an 'enhancer' effect when combined with β-lactams bound to PBP3. This study assessed the in vitro activity of NAC alone and in combination with β-lactams against IMP-type metallo-β-lactamase-producing and ESBL-producing Enterobacterales isolated in Japan. Methods: The MICs for the clinical isolates in Japan were determined and time kill studies were performed. IMP and ESBL genes were detected by PCR. The MICs were determined by broth microdilution method following CLSI methodology. β-lactams and NAC were tested as a ratio of 1:1. Time kill profiles were also studied according to CLSI methodology. Results: The MIC50 /MIC90 s of NAC alone against 112 IMP-producing Enterobacterales and 154 ESBL-producing Enterobacterales were 2/ >32 and 2/8 mg/L, respectively. Regarding the MICs of cefepime (FEP)/NAC and aztreonam (ATM)/NAC against IMP-producing isolates, the MIC90 s were 2 and 1 mg/L and the MIC ranges were 0.06 - 32 and 0.06 - 4 mg/L, respectively. The MIC90 s of FEP/NAC and ATM/NAC against ESBL-producing isolates were 0.5 and 1 mg/L. These MIC90 s of β-lactam/NAC against IMP-producing and ESBL-producing isolates were significantly lower than those of β-lactam alone (>128 mg/L). The highest MIC of ATM/NAC against IMP-producing isolates was lower than that of FEP/NAC. In addition, bactericidal activities of β-lactam/NAC were observed at the lower concentration of β-lactam compared to that of β-lactam alone. Conclusion: NAC in combination with β-lactams showed excellent in vitro activities against not only ESBL-producing Enterobacterales but also IMP-producing Enterobacterales isolated in Japan. ATM/NAC tended to show higher antimicrobial effect against IMP-producing isolates by the enzyme stability of ATM. These results support the complex activities of NAC which works as a β-lactamase inhibitor, an antibacterial agent and also an enhancer when combined with β-lactams. Furthermore, these will be useful for selecting a partner β-lactam for NAC. Disclosures: Yu Nagira, MS, Meiji Seika Pharma Co., Ltd. (Employee) Keiko Yamada, BS, Meiji Seika Pharma Co., Ltd. (Employee) Hayato Okade, Ph.D, Meiji Seika Pharma Co., Ltd. (Employee) Nami Senju, BS, Meiji Seika Pharma Co., Ltd. (Employee) Yuko Tsutsumi, MS, Meiji Seika Pharma Co., Ltd. (Employee) Yuji Tabata, Ph.D, Meiji Seika Pharma Co., Ltd. (Employee)